Discursive polarization strategies of Spanish (ultra)conservative digital media in news about feminism - Arrieta Castillo, Carolina (Estudios sobre el Mensaje Periodístico, 2025)
Journalism serves as a sounding board for political ideas and helps shape public debate. Feminism and the critique it faces from far-right parties are among the central topics in that debate. This article analyzes the coverage of feminism by five Spanish (ultra-)conservative digital media outlets, aiming to understand whether this media ecosystem contributes to the dissemination of antifeminism and digital misogyny in public discourse. A mixed-method content and discourse analysis, both qualitative and quantitative, was conducted on 200 journalistic pieces from the outlets La Razón, Libertad Digital, Okdiario, The Objective, and Vozpópuli. The sample was collected in reverse chronological order starting from December 31, 2023, with the goal of selecting 40 journalistic pieces from each outlet. The coding sheet includes categories such as types of representation, themes and commonplaces of the manosphere and feminism, and journalistic conventions and practices. The results indicate a non-positive representation of feminism, where the outlets ─except for The Objective─ align more closely with the arguments of the manosphere than with feminist agenda topics. All the outlets employ journalistic and discursive strategies ─such as the inclusion of irrelevant sources, evaluative headlines, or the use of disparaging language─ that resemble pseudojournalistic practices. Discursive polarization strategies are recurrent in the news coverage by (ultra)conservative digital media when disseminating an antifeminist agenda.
Keywords: antifeminism; media discourse; manosphere; conservative media; polarization